Adiabatic Thermal Study of Butanol and Its Derivatives as Possible Component of Red Oil With Nitric Acid in Post-Treatment - XU Xiao-qin; LIU Wei; YU Yong-bin; WU Rui-cai; TANG Shuang-ling (He huaxue yu fangshe huaxue, 2024)
The exothermic behaviors of butanol, butyraldehyde, butanone, and butyric acid with nitric acid were studied by adiabatic accelerating rate calorimeter(ARC), and the test results were compared and analyzed, and the system risk was evaluated by THI index method. The results show that under the condition of the zero oxygen balance, butyraldehyde-HNO3 system has the most obvious self-exothermic. When the butyraldehyde content is only 0.14 g, the adiabatic temperature of the system rises to 118.4 ℃ and the heat release amount is 776.6 J/g; butanol-HNO3 system begins to emit heat at about 40.2 ℃, and the highest temperature in the exothermic stage of self-reaction reaches 145.7 ℃ and the maximum pressure reaches about 34 bar(1 bar=105 Pa). Butanone-HNO3 system releases heat from 50 ℃ to 136 ℃, and the amount of heat released is 564.0 J/g. No exothermic point is observed in butyric acid-HNO3 system in the temperature range of less than 140.0 ℃. With the increase of nitric acid concentration(2.0→6.0 mol/L), the risk of butanol-HNO3 system increases from medium to high level. The risks of reaction systems of butanol, butyraldehyde, butanone and butyric acid with 4.0 mol/L HNO3 are at higher, higher, middle and middle levels.